Adherence to heme iron gummy supplementation among children 6 to 8 years of age in the district of Ate, Lima - Guija-Guerra, Henry (2022)
Objective: To determine the adherence to heme iron gummy supplementation among children 6 to 8 years of age in the district of Ate, Lima. Materials and methods: A purposive non-probability sampling of 50 children 6 to 8 years of age, of both sexes, registered in the municipality of Ate. The study included children with no anemia, mild anemia and moderate anemia. The hemoglobin level was determined at the beginning and end of the intervention. Each child ingested a heme iron gummy (9 mg elemental iron) for four months. Results: Adherence to heme iron gummies consumption was 100 %; none of the children reported side effects and all of them liked the taste of the gummies. Children with moderate anemia, mild anemia and no anemia had a hemoglobin concentration of 10.48 ± 0.48 g/dL and 11.43 ± 0.38 g/dL, 11.21 ± 0.14 g/dL and 12.17 ± 0.51 g/dL, and 11.68 ± 0.13 g/dL and 12.57 ± 0.53 g/dL at the beginning and end of the intervention, respectively. The p value in all groups was statistically significant (p = 0.000). Out of the children with mild anemia, 94.74 % achieved normal hemoglobin levels. Conclusions: All age groups had good adherence to heme iron gummies consumption and increased their hemoglobin levels.